2018
DOI: 10.1111/dme.13865
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise and non‐insulin glucose‐lowering therapies in the management of Type 2 diabetes mellitus: a clinical review

Abstract: In the UK the National Institute of Health and Care Excellence (NICE) advocates intensive lifestyle programmes that attain the levels of daily physical activity set out by the Chief Medical Officer as a first‐line strategy for improving the health of people at risk of developing diabetes or reducing the risk of development of Type 2 diabetes. For people with Type 2 diabetes, lifestyle measures complement pharmacological treatments that include both oral and injectable therapies. In line with this, NICE guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 66 publications
(88 reference statements)
0
14
0
Order By: Relevance
“…Finally, several studies have recommended the utilization of PA for T2DM patients. 13,57,68,85,122,154,155,[185][186][187][188][189][190] The requirement for integrating regular exercise as a component of a patient's lifestyle, including into daily activities, should be underlined. 185 Exercise is frequently recommended in the management of diabetes because it can support and improve glycemic control.…”
Section: Non-rct)mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, several studies have recommended the utilization of PA for T2DM patients. 13,57,68,85,122,154,155,[185][186][187][188][189][190] The requirement for integrating regular exercise as a component of a patient's lifestyle, including into daily activities, should be underlined. 185 Exercise is frequently recommended in the management of diabetes because it can support and improve glycemic control.…”
Section: Non-rct)mentioning
confidence: 99%
“…68 An exercise is also recommended for individuals who are at risk of developing or already have T2DM. 186 It is commonly one of the primary management approaches recommended for people newly diagnosed with T2DM. Exercise is also a crucial component of obesity prevention if combined with other lifestyle modification.…”
Section: Non-rct)mentioning
confidence: 99%
“…All included animal studies in this systematic review met the minimum requirements for publication using the ARRIVE guidelines checklists with 20 questions. Briefly, the median score range of all included studies was 15 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) out of a possible score of 20. The introduction domain had a median score of 4 (4-4) out of the possible score of 4 (overall agreement 100%, kappa = 1) whilst the methods domain had a median score of 6 (2-9) out of a possible score of 9 (overall agreement 88.89%, kappa = 0.76).…”
Section: Risk Of Bias and Quality Of The Studiesmentioning
confidence: 99%
“…Several studies have demonstrated that improving blood glucose control can revert diabetes-associated complications, especially by complementing antidiabetic drugs with lifestyle modification intervention, such as regular physical activity [13][14][15]. However, the major challenge has been the limitation of evidence showing the long-term effectiveness of antidiabetic drugs, this coupled with so few individuals that can maintain consistent physical activity could explain the continued rise in new cases of diabetes over the past decades [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…More evidence is available for interactions between physical activity and drugs but, again, this has tended to concentrate on supervised exercise and has not looked at whether the addition of drug therapy impacts on adherence to exercise advice. Eckstein et al [30] have recently reviewed the interactions between exercise and non-insulin glucose-lowering therapies. Table 1 summarizes what is known.…”
Section: Interaction Of Physical Activity and Drugsmentioning
confidence: 99%